2017
DOI: 10.1002/nbm.3715
|View full text |Cite
|
Sign up to set email alerts
|

CEST imaging of fast exchanging amine pools with corrections for competing effects at 9.4 T

Abstract: Chemical exchange saturation transfer (CEST) imaging of fast exchanging amine protons at 3 ppm offset from the water resonant frequency is of practical interest but quantification of fast exchanging pools by CEST is challenging. To effectively saturate fast exchanging protons, high irradiation powers need to be applied, but these may cause significant direct water saturation (DS) as well as non-specific semi-solid magnetization transfer (MT) effects and thus decrease the specificity of the measured signal. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 57 publications
(167 reference statements)
3
63
0
Order By: Relevance
“…Various types of pathology can alter tissue properties, particularly, water relaxation times, water content, and semi-solid MTC content. Previous studies showed that APT signal apparently increases with T 1w , but the relationship is not linear (42, 65). Notably, the positive correlation no longer exists at the high RF saturation power level, and it seems that the APT signal is not associated with T 1w at 2 μT, as was used in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Various types of pathology can alter tissue properties, particularly, water relaxation times, water content, and semi-solid MTC content. Previous studies showed that APT signal apparently increases with T 1w , but the relationship is not linear (42, 65). Notably, the positive correlation no longer exists at the high RF saturation power level, and it seems that the APT signal is not associated with T 1w at 2 μT, as was used in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Specifically for EMR, CEST data with Δ ω from –6500 to –3500 Hz and 3500 to 6500 Hz and ω 1 of 3.6 μT, and with Δ ω from –4000 to –2500 Hz and 2500 to 4000–Hz and ω 1 of 1.0 μT, were fitted to a two‐pool MT model (see Appendix). The reference signals in an offset range from –5 to 5 ppm were then estimated using the fitted parameters, and used for the calculation of the above metrics. As a result of the relatively homogeneous B 1 field in rat brain, ω 1 used to calculate tan θ was from nominal values.…”
Section: Methodsmentioning
confidence: 99%
“…In CEST imaging of fast‐exchanging amines, which is usually performed at relatively high irradiation powers (e.g. >3 μT), the CEST peak shifts, which makes it difficult to identify specific CEST effects …”
Section: Introductionmentioning
confidence: 99%
“…However, distinct from the narrow and specific peaks prevalent in MRS, CEST peaks, especially those from fast‐exchanging pools (e.g. glutamate at 3 ppm 2 ), are broad and often overlap . Therefore, the CEST signal at 2 ppm may contain contributions from both intermediate‐exchanging amines at 2 ppm and other nearby fast‐exchanging pools.…”
Section: Introductionmentioning
confidence: 99%